(untitled) (Journal of the College of Basic Education, 2022)
This study deals with group of pronunciations that are asserted by Al-Fayoomi in Al-Misbah Al-Muneer Dictionary. it shows the semantic transferring idiomatically and linguistically, and show the semantic pronunciation transfers from indicating something In somewhere to another thing in somewhere else may be there is a relation between them or it differs from it, May be the semantic transferring is intended or not but in both there, are certain reasons and motives. Thus this study exposes the pronunciations that have connection with their semantics, and it is named by scientists as figurative term, This study also explains transferring process that affected these pronunciations, each in its chapter as it is mentioned by the scientist’s savings, including Al-Fayoomi. They are compared to one another to show the similarity between the two semantic, and the semantic transferring through mentioning the original meaning for pronunciation.